ECB policy and Eurozone fragility: Was de grauwe right? - Saka, Orkun; Fuertes, Ana Maria; Kalotychou, Elena (My University, 2015)
Paul De Grauwe's Eurozone fragility hypothesis states that sovereign debt markets in a monetary union without a lender-of-last-resort are vulnerable to self-fulfilling dynamics fuelled by pessimistic investor sentiment that can trigger default. We test this contention by applying an eclectic methodology to a two-year window around Mario Draghi's "whatever-it-takes" pledge that can be understood as the implicit announcement of the Outright Monetary Transactions (OMT) program. A principal components analysis reveals that the perceived commonality in default risk among peripheral and core Eurozone sovereigns increased after the announcement. An event study reveals significant pre-announcement news transmission from Spain to Italy, France, Belgium and Austria that clearly dissipates post-announcement. Country-specific regressions of CDS spreads on systematic risk factors reveal frequent days of large adverse shocks affecting simultaneously those five Eurozone countries, but only during the pre-announcement period. Altogether these findings support the fragility hypothesis and endorse the OMT program.
Keywords: European central bank; Eurozone fragility; Outright monetary transactions; Self-fulfilling dynamics; Sovereign debt